A Study on Definitive Role of Smoking Over Alcohol on Peptic Ulcer Disease.: Life Sciences-General medicine - S, Dr Roshini; S, Dr Suresh Kanna; Siri, Dr Kavuru Naga; Thomas, Dr Sunil George (International Journal of Life Science and Pharma Research, 2023)
Peptic ulcer disease is characterized by erosive lesions of the lining of the gastrointestinal tract, the mucosa being damaged by the action of Hydrochloric acid and Pepsin, spread deeply into the submucosa and lamina propria, mainly of the stomach and duodenum. Smoking, directly and indirectly, affects the lining of the stomach and duodenum, increases the duodenal gastric reflux with mucosal damage, decreases prostaglandin secretion, and slow and consistent exposure radically affects the prognosis allied with detained healing. Furthermore, the effects of smoking are related to long-term exposure, accelerating chronic ulcers with slow healing. This study focuses on a defined number of patients and tries to fulfill the lack of significance of smoking in other studies previously established. It stands out from other studies because most of the studies conducted give the general impression that alcohol consumption is more associated with peptic ulcers; this study is aimed to investigate as well as compare the role of smoking and alcohol, and the novelty of this study is intended to confirm the strong and indispensable capacity of smoking in the causation and complications of peptic ulcer disease, focusing on patients who are already known and newly diagnosed, to elaborate our investigation on how despite treatment, smoking proves to be a significant cause delaying healing and affecting prognosis. The study group of hundred patients first and foremost revealed that only 50% to 60% were aware of their peptic ulcer disease, accounting for about fiftythree patients. And 92% of the patient’s presented with hematemesis, coexisting with heartburn, regurgitation, Abdominal pain, or epigastric pain. This retrospective study of 100 patients distinctly revealed that the patients suffering from peptic ulcer disease had a compelling etiological factor as smoking, while alcohol was only an aggravating cofactor.